A SCOPING REVIEW ON THE ORIGIN, STATUS AND PROGRESS OF POLICY ORIENTED ONE HEALTH RESEARCH IN INDIA AND THE WAY FORWARD - Gururaj Makarabbi; ANA RAJ; Suresh Ramanan; Anubha Pathak; Shanthya M S (Journal of Animal and Plant Sciences, 2023)
Zoonotic infectious diseases like Zika, Ebola, Severe Acute Respiratory Syndrome (SARS), Middle East Respiratory Syndrome (MERS) and the very recent Coronavirus Disease (COVID-19) can leap from one species to another and within the same species by constantly mutating to defy therapeutics and vaccines. The SARS-CoV-2 is emerging to be closely related to bat coronaviruses, highlighting the need of One Health approach to combat new disease threats that affects both animals and human beings. One Health is a collaborative, multi-sectoral and trans-disciplinary approach - working at the local, regional, national, and global levels, with the goal of achieving optimal health outcomes recognizing the interconnection between people, animals, plants and their shared environment. Therefore, One Health can be considered as a global approach to maintain health of human beings, animals and ecosystem. The present study plots the One Health publications available in Web of Science (WoS) database from 1997 to 2021. WoS provides access to databases that supplies reference and citation data from research publications. Globally, a total of 4397 publications were published. In Indian context, about 230 scientific literatures were published and only 94 publications were found relevant to policy makers. Relevance to policy-makers was judged by the presence of policy implications in the research publication. Further, data were analysed using bibliometrix R-package to evaluate research publications of authors, the annual growth of research publications and citation analysis to understand the status of One Health research in India. The annual growth rate of publications in India was 47.48 per cent with collaboration index 6.58, which is greater than global collaboration index. Three-fields plot exhibited that in Guru Angad Dev Veterinary and Animal Science University (GADVASU), Ludhiana, dedicated research on One Health is being carried out with 13 publications on One Health. The collaboration network analysis found that Indian authors are highly collaborative with researchers from Australia, USA and Germany. In addition to these formal collaborations, there is opportunity to strengthen informal collaboration through digital platforms like Google Scholar, ResearchGate, LinkedIn, Facebook, Google+, Twitter etc. With judicious use, they could be used to sprout fruitful collaborations. Thus, the trend of policy oriented One Health research in India was analysed to illuminate on the possible researchable themes and future line of works.
Keywords: One Health; multidisciplinary; zoonosis; collaboration; health policy; India